Demand of international visitors to the Kilim Karst Geoforest Park Langkawi - Matthew, Nitanan Koshy; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (2014)
Kilim Karst Geoforest Park (KKGP) offers pristine nature based attractions to visitors. Apart from local visitors, the park receives many international visitor arrivals from all over the world. The demand model of international visitors to the park can be developed using one of the common environmental valuation techniques, the Travel Cost Method (TCM). The Individual Travel Cost Model (ITCM) has been employed in the research. Thus, the article develops the demand model of international visitors to the KKGP and determines the economic value of the park. Structured questionnaire and face-to-face data collection method are employed to obtain the primary data from 330 international visitors using the purposive sampling technique. The analysis using the Poisson regression shows that the travel cost, time cost, quality of site, age and education variables, are significant at 95% confidence level. The consumer surplus per visitor/year is found to be €216 or RM 864, whilst the economic value of the park is estimated to be €27 million or RM 108 million. Findings from the study will be useful for Langkawi Development Authority (LADA) to justify on monetary allocations made by the federal government for the tourism development at the park.